Nomogram model based on preoperative serum thyroglobulin and clinical characteristics of papillary thyroid carcinoma to predict cervical lymph node metastasis - Chang, Qungang; Zhang, Jieming; Wang, Yaqian; Li, Hongqiang; Du, Xin; Zuo, Daohong; Yin, Detao (Frontiers in Endocrinology, 2022)
Objective: Preoperative evaluation of cervical lymph node metastasis (LNM) in papillary thyroid carcinoma (PTC) has been one of the serious clinical challenges. The present study aims at understanding the relationship between preoperative serum thyroglobulin (PS-Tg) and LNM，and intend to establish nomogram models to predict cervical LNM. Methods: The data of 1324 PTC patients were retrospectively collected and randomly divided into training cohort (n=993) and validation cohort (n=331). Univariate and multivariate logistic regression analyses were performed to determine the risk factors of central lymph node metastasis (CLNM) and lateral lymph node metastasis (LLNM). The nomogram models were constructed and further evaluated by 1,000 resampling bootstrap analyses. The receiver operating characteristic curve (ROC curve), calibration curve and decision curve analysis (DCA) of the nomogram models were carried out for the training, validation and external validation cohorts. Results: Analyses revealed that age,male , the maximum tumor size>1cm, PS-Tg>= 31.650ng/ml, extrathyroidal extension (ETE) and mutifocality were the significant risk factors for CLNM in PTC patients. Similarly, such factors as maximum tumor size>1cm, PS-Tg>= 30.175ng/ml, CLNM positive, ETE and mutifocality were significantly related to LLNM. Two nomogram models predicting the risk of CLNM and LLNM were established with a favorable C-index of 0.801 and 0.911 respectively. Both nomogram models demonstrated good calibration and clinical benefits in training and validation cohorts. Conclusion: PS-Tg level is an independent risk factor for both CLNM and LLNM. The nomogram based on PS-Tg and other clinical characteristics are effective for predicting cervical LNM in PTC patients.